Preparation method and application of complex capable of efficiently chelating metal ions
By modifying ethylenediamine disuccinic acid on the membrane surface and forming PVA-g-EDDS, the problems of poor biodegradability and limited selectivity of traditional chelating agents in heavy metal wastewater treatment are solved, and efficient and green heavy metal ion interception and treatment are achieved. Effect.
Patent Information
- Application Number
- CN202411520466.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In the prior art, when treating heavy metal wastewater, traditional chelating agents have poor biodegradability and are toxic, and the membrane treatment selectivity is limited, making it difficult to effectively remove high or low concentrations of heavy metal ions.
Using ethylenediamine disuccinic acid as the reference material, it is prepared by different molar ratios of polyvinyl alcohol, ethylenediamine disuccinic acid, catalyst and reaction medium. After a specific temperature and time reaction, a new water-soluble polymer PVA is formed- g-EDDS and dialyzed through a dialysis membrane to obtain a complex that efficiently chelates metal ions.
It improves the retention of metal ions, can effectively treat heavy metal wastewater of high or low concentrations, significantly improves the wastewater treatment efficiency, and has good biocompatibility and recyclability, reducing environmental pollution.
Smart Images

Figure CN119390878A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of complex preparation, and in particular relates to a preparation method of a complex for efficiently chelating metal ions and application thereof. Background Art
[0002] Heavy metals have caused serious damage to the natural environment. A large amount of waste liquid and waste residue produced in industry contains a large number of heavy metal ions. If not properly handled, it will not only fail to eliminate the pollution of heavy metal ions to the environment, but will also cause secondary pollution to the environment. For example, in battery manufacturing, electroplating and nuclear industry, waste liquid and waste residues that produce highly radioactive metal ions urgently need to explore an effective green purification treatment technology.
[0003] At present, industrial waste containing heavy metals is either treated by simple landfill or by ordinary chemical precipitation, that is, precipitation after treatment with chelating agents such as EDTA, DTPA, and NTA. Although it can temporarily eliminate ground pollution sources, traditional chelating agents have poor biodegradability and certain toxicity, and the damage to groundwater sources or underground microbial environments is irreversible. Membrane treatment is a very promising method. It has the advantages of high efficiency, low composition and recyclability, but it also has limited selectivity and these polymers must be chemically stable, have high affinity for target metal cations, and have low affinity for ultrafiltration membranes. Therefore, the development of new and affordable chelating agents to enhance the "high efficiency and green" characteristics of chelating and extracting metal ions in membrane treatment processes is a hot topic in this field. However, the cellulose filtration membranes widely used in the market are very inefficient in treating high or low concentrations of heavy metal wastewater. For high-concentration heavy metal wastewater, multi-stage membrane treatment is required to make the effluent meet the standards, otherwise it is easy to cause the accumulation of metal hydroxides, which greatly reduces the service life. However, low-concentration heavy metal wastewater, due to the concentration effect and small metal ion particle size, can easily penetrate the filter membrane, resulting in failure of heavy metal retention. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the present invention discloses
[0005] The invention discloses a preparation method of a complex for efficiently chelating metal ions. The method comprises the following steps: S1: taking ethylenediamine disuccinic acid as a reference substance, and respectively having different molar ratios between polyvinyl alcohol, ethylenediamine disuccinic acid, a catalyst and a reaction medium and the ethylenediamine disuccinic acid; weighing a certain amount of ethylenediamine disuccinic acid; preparing a polyvinyl alcohol solution according to the molar ratio with the ethylenediamine disuccinic acid; and weighing the ethylenediamine disuccinic acid, the catalyst and the reaction medium; S2: adding the weighed ethylenediamine disuccinic acid, the catalyst and the reaction medium to the polyvinyl alcohol solution at a certain temperature, stirring and mixing, to obtain a mixed solution; S3: naturally cooling the mixed solution to a certain temperature, maintaining the temperature, and gradually adding a certain amount of initiator to the mixed solution within a certain reaction time for stirring, to obtain an intermediate solution; S4: dialyzing the intermediate solution for a period of time, to obtain a complex PVA-g-EDDS.
[0006] Furthermore, the catalyst in S2 is triphenylphosphine, the reaction medium is dimethyl sulfoxide, and the initiator in S3 is diethyl azodicarboxylate.
[0007] Further, the molar ratio of polyvinyl alcohol to ethylenediamine disuccinic acid is in the range of 2-1, the molar ratio of triphenylphosphine to ethylenediamine disuccinic acid is in the range of 0.1-1.1, and the molar ratio of diethyl azodicarboxylate to ethylenediamine disuccinic acid is in the range of 0.5-2.5.
[0008] Furthermore, the mixing temperature in S2 is 80-140°C, which is reduced to 20-60°C in S3, and the reaction time is 2-12h.
[0009] Further, in S3, the temperature is lowered to 30-40°C and the reaction time is 2-4h.
[0010] Furthermore, the finally prepared PVA-g-EDDS is dialyzed using a dialysis membrane, the molecular weight cutoff of the dialysis membrane is 500-2000Da, and the dialysis time is 1-3 days.
[0011] The present invention discloses an application of a complex for efficiently chelating metal ions, using any one of the PVA-g-EDDS prepared as described above, which comprises:
[0012] PVA-g-EDDS is used for membrane filtration of cobalt ions, nickel ions, copper ions, zinc ions, lead ions, zinc ions, calcium ions and manganese ions in wastewater.
[0013] Furthermore, PVA-g-EDDS was used to treat wastewater in combination with an ultrafiltration membrane, and the transmembrane pressure was set to 0.1-2.0 bar.
[0014] Beneficial effects of the present invention:
[0015] The present invention draws on the principle of coordination chemistry, and chemically modifies biocompatible and non-toxic polyvinyl alcohol by modifying the membrane surface with ethylenediamine disuccinic acid, thereby obtaining a new water-soluble polymer, called PVA-g-EDDS. The present invention improves the retention of metal ions by adding PVA-g-EDDS to the wastewater. The polymer chelating agent has multiple strong chelating sites on a molecular chain and can treat wastewater with high concentrations of metal ions. At the same time, for low-concentration wastewater, it can also effectively chelate metal ions, and the molecular weight is increased after chelation, so that the metal chelate is retained by the membrane, which greatly improves the wastewater treatment efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a flow chart of the preparation method of the complex for efficiently chelating metal ions in the embodiment of the present application. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the specific implementation modes of the present invention will be clearly and completely described below.
[0018] The present application discloses a method for preparing a complex for chelating metal ions with high efficiency, which comprises the following steps: S1: taking ethylenediamine disuccinic acid as a reference substance, polyvinyl alcohol, ethylenediamine disuccinic acid, a catalyst and a reaction medium have different molar ratios with ethylenediamine disuccinic acid, weighing a certain amount of ethylenediamine disuccinic acid, preparing a polyvinyl alcohol solution according to the molar ratio with ethylenediamine disuccinic acid, and weighing the ethylenediamine disuccinic acid, the catalyst and the reaction medium, S2: adding the weighed ethylenediamine disuccinic acid, the catalyst and the reaction medium to the polyvinyl alcohol solution at a certain temperature, stirring and mixing, to obtain a mixed solution, S3: naturally cooling the mixed solution to a certain temperature, maintaining the temperature, and gradually adding a certain amount of initiator to the mixed solution within a certain reaction time for stirring, to obtain an intermediate solution, and S4: dialyzing the intermediate solution for a period of time, to obtain a complex PVA-g-EDDS. The present invention draws on the principle of coordination chemistry, and chemically modifies biocompatible and non-toxic polyvinyl alcohol by modifying the membrane surface with ethylenediamine disuccinic acid, thereby obtaining a new water-soluble polymer, called PVA-g-EDDS. The present invention improves the retention of metal ions by adding PVA-g-EDDS to the wastewater body. The polymer chelating agent has multiple strong chelating sites on a molecular chain and can treat metal ion wastewater with high concentration. At the same time, for low-concentration wastewater, it is also effective in chelating metal ions, and the molecular weight is increased after chelation, so that the metal chelate is retained by the membrane, which greatly improves the wastewater treatment efficiency. Compared with traditional EDTA chelating agents, EDDS can be decomposed more environmentally friendly without environmental pollution problems, and EDDS is easier to combine with metal ions, which will greatly improve the chelating ability of oligomeric PVA. At the same time, it has the characteristics of being recyclable, economical and more environmentally friendly.
[0019] As an embodiment, the catalyst in S2 is triphenylphosphine, the reaction medium is dimethyl sulfoxide, and the initiator in S3 is diethyl azodicarboxylate. Triphenylphosphine can effectively activate the initiator diethyl azodicarboxylate, thereby promoting the generation of free radicals, improving the reaction activity, and achieving a better reaction rate at a lower temperature, reducing energy consumption and reducing the possibility of side reactions. Dimethyl sulfoxide, as a polar aprotic solvent, has good solubility and can dissolve diethyl azodicarboxylate and triphenylphosphine and other reaction components well, ensuring full contact and uniform mixing between reactants. Diethyl azodicarboxylate can decompose to generate two free radicals under heating conditions. By controlling the temperature and the addition rate, the generation rate of free radicals can be effectively managed, thereby achieving fine control of the reaction process.
[0020] As an embodiment, the molar ratio of polyvinyl alcohol to ethylenediamine disuccinic acid is in the range of 2-1, the molar ratio of triphenylphosphine to ethylenediamine disuccinic acid is in the range of 0.1-1.1, and the molar ratio of diethyl azodicarboxylate to ethylenediamine disuccinic acid is in the range of 0.5-2.5.
[0021] By adjusting the molar ratio between polyvinyl alcohol and ethylenediamine disuccinic acid, an appropriate amount of ethylenediamine disuccinic acid groups can be introduced into the polyvinyl alcohol chain, thereby improving the grafting efficiency. If the molar ratio is too low, close to 1:1, the grafting sites on the polyvinyl alcohol chain are not enough to accommodate enough EDDS. If the molar ratio is too high, close to 2:1, it will cause the excess polyvinyl alcohol and ethylenediamine disuccinic acid to compete with each other, affecting the grafting effect. The amount of triphenylphosphine used as a catalyst directly affects the activity of the reaction. The appropriate molar ratio can ensure that the reaction is neither too violent nor too slow, thereby better controlling the reaction rate. If the amount of triphenylphosphine is too small, the initiator cannot be effectively activated, resulting in incomplete reaction. If the amount of triphenylphosphine is too large, it will cause unnecessary side reactions. Therefore, choosing a suitable molar ratio can minimize the formation of by-products. The appropriate ratio of diethyl azodicarboxylate to ethylenediamine disuccinic acid helps to balance the kinetics of the reaction and avoid runaway reactions caused by excessive or low free radical concentrations. Excessive free radical concentrations lead to polyvinyl alcohol chain breakage, while too low concentrations slow the reaction.
[0022] As an embodiment, the mixing temperature in S2 is 80-140°C, the temperature in S3 is reduced to 20-60°C, and the reaction time is 2-12h. Preferably, the temperature in S3 is reduced to 30-40°C, and the reaction time is 2-4h. Higher temperatures can accelerate the diffusion between reactants and promote the interaction between polyvinyl alcohol and ethylenediamine disuccinic acid, thereby accelerating the speed of the grafting reaction. This means that more chemical reactions can be completed in a shorter time, improving production efficiency. Heating can increase the kinetic energy of molecules, making it easier for reactant molecules to collide and react, thereby increasing the activity of the overall reaction. This is particularly important for chemical reactions that require higher energy to start. Lowering the temperature in the S3 stage can better control the reaction rate and avoid side reactions or overreactions caused by excessive temperature. By gradually adding initiators and reacting at lower temperatures, it can be ensured that the reaction is carried out in a milder environment. Lower temperatures help reduce the formation of by-products, thereby improving the purity of the product. In addition, the appropriate temperature can prevent excessive crosslinking or breakage of polyvinyl alcohol chains, ensuring that the product has good structural stability and expected performance. Compared with high temperature reactions, low temperature reactions usually require less energy input, which can save energy consumption and reduce production costs. Longer reaction times can ensure that the reactants have enough time to interact with each other, thereby achieving a higher conversion rate. This helps to increase the yield of the product and ensure that most of the raw materials are fully utilized. However, too long a reaction time will lead to unnecessary energy consumption and increased production costs. A reaction time of 2-4 hours can balance the sufficiency of the reaction and production efficiency, ensuring that high-quality products are obtained in a shorter time.
[0023] As an embodiment, the PVA-g-EDDS finally prepared is dialyzed using a dialysis membrane, the molecular weight cutoff of the dialysis membrane is 500-2000Da, and the dialysis time is 1-3 days. Preferably, the molecular weight cutoff of the dialysis membrane is 800-1200Da, and the dialysis time is 2 days. The dialysis membrane can selectively allow small molecules to pass through according to its molecular weight cutoff, while preventing the passage of macromolecules. Therefore, the small molecule by-products produced during the synthesis process can be effectively removed by dialysis to improve the purity of the product. The molecular weight cutoff of 500-2000Da can ensure that the macromolecular structure of PVA-g-EDDS will not be destroyed, while removing unnecessary small molecules, thereby protecting the integrity and functionality of the product. The dialysis time is 1-3 days, which can be adjusted according to actual conditions to ensure that small molecule impurities are thoroughly removed while avoiding the waste of resources caused by excessive dialysis. Longer dialysis time can further improve the purity of the product. Selecting a molecular weight cut-off range of 800-1200Da allows for more precise removal of unwanted small molecule impurities while ensuring that the macromolecular structure of PVA-g-EDDS is not affected. This selectivity helps improve the purity and quality of the product.
[0024] The present application discloses an application of a complex for efficiently chelating metal ions, using any one of the PVA-g-EDDS prepared as described above, which includes: PVA-g-EDDS is applied to membrane filtration of cobalt ions, nickel ions, copper ions, zinc ions, lead ions, zinc ions, calcium ions and manganese ions in wastewater.
[0025] As an embodiment, PVA-g-EDDS is used in conjunction with an ultrafiltration membrane to treat wastewater, and the transmembrane pressure is set to 0.1-2.0 bar. Preferably, the transmembrane pressure is set to 0.5-0.8 bar.
[0026] Example:
[0027] Example 1
[0028] First, 3.65 g of ethylenediamine disuccinic acid was weighed. According to the molar ratio of polyvinyl alcohol to ethylenediamine disuccinic acid being 2-1, the molar ratio of triphenylphosphine to ethylenediamine disuccinic acid being 0.1-1.1, and the molar ratio of diethyl azodicarboxylate to ethylenediamine disuccinic acid being 0.5-2.5, 3.28 g of triphenylphosphine, 4.35 g of diethyl azodicarboxylate and DMSO were weighed as solvent to prepare a polyvinyl alcohol solution.
[0029] At 120°C, a polyvinyl alcohol solution (500 mg, 10 mL DMSO, 11.4 mmol, 1 eq) was added to a mixture containing triphenylphosphine (3.28 g, 12.5 mmol, 1.1 eq), ethylenediamine disuccinic acid (3.65 g, 12.5 mmol, 1.1 eq) and 50 mL dimethyl sulfoxide (DMSO). At 30°C, diethyl azodicarboxylate (4.35 g, 25 mmol, 2.2 eq) was gradually added over 2 hours. The resulting solution was then stirred overnight at room temperature. The reaction medium was transferred to a dialysis tube (MWCO≈1000 Da) and dialyzed with DMSO for two days to remove all organic components except the functionalized polymer. Finally, it was dialyzed with water to remove all DMSO, and the yield of PVA-g-EDDS was 90%.
[0030] First, a solid sample was prepared: a certain amount of metal ions (Co2+2+) were weighed, and then a chelating agent was weighed according to a molar ratio of metal cations to EDDS of 1:4.
[0031] The weighed chelating agent was dissolved in water, and then the metal cation solution was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was detected and analyzed by ICP-MS. The test results showed that the complex adsorption rate of Co(II) was 86%.
[0032] Example 2
[0033] The PVA-g-EDDS of Example 1 was used as a chelating agent;
[0034] First, a solid sample was prepared: a certain amount of metal ions (Co2+, Ni2+, Cs+) were weighed, and then a chelating agent was weighed according to a molar ratio of metal cations to EDDS of 1:4.
[0035] The weighed chelating agent was dissolved in water, and then the metal cation solution was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was analyzed by ICP-MS. The test results showed that the complex adsorption rate of Ni (II) was 96%, and that of Co (II) was 86%.
[0036] Example 3
[0037] The PVA-g-EDDS of Example 1 was used as a chelating agent;
[0038] First, a solid sample was prepared: a certain amount of metal ions (Co2+, Ni2+) were weighed, and then a chelating agent was weighed in a molar ratio of 1:1 between metal cations and EDDS.
[0039] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was analyzed by ICP-MS. The test results showed that the complex adsorption rate of Ni (II) was 50%, and that of Co (II) was 35%.
[0040] Example 4
[0041] The PVA-g-EDDS of Example 1 was used as a chelating agent;
[0042] First, a solid sample was prepared: a certain amount of metal ions (Pb(II), Cu(II), Cd(II), Zn(II)) were weighed, and then a chelating agent was weighed according to a molar ratio of metal cations to EDDS of 1:4.
[0043] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was detected and analyzed by ICP-MS. The test results showed that the complex adsorption rate was greater than 97%.
[0044] Example 5
[0045] The PVA-g-EDDS of Example 1 was used as a chelating agent;.
[0046] First, a solid sample was prepared: a certain amount of metal ions (Pb(II), Cu(II), Cd(II), Zn(II)) were weighed, and then a chelating agent was weighed according to a molar ratio of metal cations to EDDS of 1:2.
[0047] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was detected and analyzed by ICP-MS. The test results showed that the complex adsorption rate was greater than 97%.
[0048] Example 6
[0049] The PVA-g-EDDS of Example 1 was used as a chelating agent;
[0050] First, a solid sample was prepared: a certain amount of metal ions (Pb(II), Cu(II), Cd(II), Zn(II)) were weighed, and then a chelating agent was weighed in a molar ratio of 1:1 between metal cations and EDDS.
[0051] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred for one hour at room temperature, and finally filtered on a porcelain membrane. The filtrate was analyzed by ICP-MS. The test results showed that the complex adsorption rates were 0% for Cd(II), 0% for Zn(II), 50% for Pb(II), and 96% for Cu(II).
[0052] Example 7
[0053] The PVA-g-EDDS of Example 1 was used as a chelating agent;
[0054] First, a solid sample was prepared: a certain amount of metal ions (Pb(II), Cu(II), Ca(II), Mn(II) were weighed, and then a chelating agent was weighed in a ratio of 1:1 between the metal cations and EDDS.
[0055] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was analyzed by ICP-MS. The test results showed that the complex adsorption rate of Cu (II) was 96%, and that of Pb (II) was 50%.
[0056] Comparative Example 1:
[0057] EDTA at a concentration of 1% was used as a chelating agent;
[0058] First, a solid sample is prepared: a certain amount of metal ions (Co2+2+) are weighed, and then a chelating agent is weighed according to a molar ratio of metal cations to EDTA of 1:4.
[0059] The weighed chelating agent was dissolved in water, and then the metal cation solution was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was detected and analyzed by ICP-MS. The test results showed that the complex adsorption rate of Co(II) was 72%.
[0060] Comparative Example 2:
[0061] EDTA at a concentration of 1% was used as a chelating agent;
[0062] First, prepare the solid sample: first weigh a certain amount of metal ions (Co2+, Ni 2 +, Cs+), and then weigh the chelating agent in a molar ratio of metal cation to EDTA of 1:4; dissolve the weighed chelating agent in water, and then add the metal cation solution, stir the mixture at room temperature for three hours, and finally filter using a ceramic membrane (Aldrich, MWCO=20kDa) with a transmembrane pressure of 0.5bar; stop filtering when the permeate accounts for 15% of the whole solution, and analyze the filtrate by ICP-MS; the test results show that the complex adsorption rates of Ni(II) are 82%, and those of Co(II) are 71%.
[0063] Comparative Example 3:
[0064] DTPA was used as a chelating agent at a concentration of 1%;
[0065] First, a solid sample was prepared: a certain amount of metal ions (Co2+, Ni2+) were weighed, and then a chelating agent was weighed in a molar ratio of 1:1 between metal cations and DTPA.
[0066] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was analyzed by ICP-MS. The test results showed that the complex adsorption rate of Ni (II) was 37%, and that of Co (II) was 31%.
[0067] Comparative Example 4:
[0068] NTA was used as a chelating agent at a concentration of 0.5%;
[0069] First, a solid sample was prepared: a certain amount of metal ions (Pb(II), Cu(II), Cd(II), Zn(II)) were weighed, and then a chelating agent was weighed according to a molar ratio of metal cations to NTA of 1:4.
[0070] The weighed chelating agent was dissolved in water, and then the metal cation was added. The mixture was stirred at room temperature for three hours, and finally filtered using a ceramic membrane (Aldrich, MWCO = 20kDa) with a transmembrane pressure of 0.5 bar. The filtration was stopped when the permeate accounted for 15% of the total solution. The filtrate was detected and analyzed by ICP-MS. The test results showed that the complex adsorption rate was greater than 72%.
[0071] Result analysis:
[0072] It can be seen from Examples 1-7 that PVA-g-EDDS can treat wastewater with high concentrations of metal ions, and can also effectively chelate metal ions, increase the molecular weight, and allow the metal chelate to be retained by the membrane. When treating wastewater with high concentrations of metal ions, PVA-g-EDDS exhibits a high metal ion retention efficiency. Even in the treatment of low-concentration wastewater, PVA-g-EDDS can still effectively chelate metal ions and allow the metal chelate to be retained by the membrane by increasing the molecular weight.
[0073] By comparing Examples 1-4 and Comparative Examples 1-4, it can be seen that traditional chelating agents such as EDTA, DTPA and NTA are used. These traditional chelating agents usually have only one chelating site, and the processing capacity for high-concentration and low-concentration wastewater is limited. When treating high-concentration metal ion wastewater, traditional chelating agents cannot completely chelate all metal ions, resulting in low processing efficiency. When treating low-concentration wastewater, the effectiveness of traditional chelating agents is also limited, and the molecular weight of metal chelates cannot be effectively increased, making it difficult to be retained by the membrane. PVA-g-EDDS shows a higher metal ion retention efficiency in high-concentration wastewater treatment because it has multiple chelating sites and can effectively chelate a large amount of metal ions. Traditional chelating agents cannot completely chelate all metal ions in high-concentration wastewater treatment, resulting in a processing efficiency that is not as good as PVA-g-EDDS. PVA-g-EDDS shows a higher metal ion retention efficiency when treating high-concentration and low-concentration wastewater, which is mainly due to the fact that it has multiple powerful chelating sites on the molecular chain, can effectively chelate metal ions, and the metal chelate is retained by the membrane by increasing the molecular weight. Traditional chelating agents such as EDTA, DTPA and NTA are relatively ineffective in treating high-concentration and low-concentration wastewater, especially in low-concentration wastewater treatment, where traditional chelating agents cannot effectively increase the molecular weight of metal chelates, making them difficult to be retained by membranes. Therefore, PVA-g-EDDS, as a polymer chelating agent, has significant advantages in wastewater treatment and can significantly improve the retention efficiency of metal ions, especially in treating high-concentration and low-concentration wastewater.
[0074] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
Claims
1. A method for preparing a complex for efficiently chelating metal ions, characterized in that: include: S1: Taking ethylenediamine disuccinic acid as a reference substance, polyvinyl alcohol, ethylenediamine disuccinic acid, a catalyst and a reaction medium have different molar ratios with ethylenediamine disuccinic acid, a certain amount of ethylenediamine disuccinic acid is weighed, a polyvinyl alcohol solution is prepared according to the molar ratio with ethylenediamine disuccinic acid, and ethylenediamine disuccinic acid, a catalyst and a reaction medium are weighed; S2: at a certain temperature, adding weighed ethylenediamine disuccinic acid, a catalyst and a reaction medium into the polyvinyl alcohol solution and stirring and mixing to obtain a mixed solution; S3: After the mixed solution is naturally cooled to a certain temperature, the temperature is maintained, and within a certain reaction time, a certain amount of initiator is gradually added to the mixed solution and stirred to obtain an intermediate solution; S4: dialyze the intermediate solution for a period of time to obtain the complex PVA-g-EDDS.
2. A method for preparing a highly efficient chelated metal ion complex according to claim 1, characterized in that: include: The catalyst in S2 is triphenylphosphine and the reaction medium is dimethyl sulfoxide; The initiator S3 is diethyl azodicarboxylate.
3. The method for preparing a highly efficient chelated metal ion complex according to claim 1, characterized in that: include: The molar ratio between polyvinyl alcohol and ethylenediamine disuccinic acid ranges from 2 to 1; The molar ratio between triphenylphosphine and ethylenediamine disuccinic acid ranges from 0.1 to 1.1; The molar ratio between diethyl azodicarboxylate and ethylenediamine disuccinic acid ranges from 0.5 to 2.
5.
4. The method for preparing a highly efficient chelated metal ion complex according to claim 1, characterized in that: include: The mixing temperature in S2 is 80-140°C; In S3, the temperature is lowered to 20-60°C and the reaction time is 2-12h.
5. The method for preparing a highly efficient chelated metal ion complex according to claim 4, characterized in that: include: In S3, the temperature is lowered to 30-40°C and the reaction time is 2-4h.
6. The method for preparing a highly efficient chelated metal ion complex according to claim 1, characterized in that: include: The finally prepared PVA-g-EDDS is dialyzed using a dialysis membrane with a molecular weight cutoff of 500-2000 Da and a dialysis time of 1-3 days.
7. An application of a complex for efficiently chelating metal ions, using any one of the PVA-g-EDDS prepared as claimed in claims 1 to 6, characterized in that: include: PVA-g-EDDS is used for membrane filtration of cobalt ions, nickel ions, copper ions, zinc ions, lead ions, zinc ions, calcium ions and manganese ions in wastewater.
8. The use of a complex for efficiently chelating metal ions according to claim 7, characterized in that: PVA-g-EDDS is used in conjunction with ultrafiltration membrane to treat wastewater, with the transmembrane pressure set at 0.1-2.0 bar.
Citation Information
Patent Citations
Method for synthesizing polymer chelating agent with polyvinyl alcohol as base chain
CN101173019A
Ethylene-vinyl alcohol-based graft copolymer particle, method for producing the same and metal ion adsorbent
JP2014159547A
Succinic acid derivative degradable chelants, uses and compositions thereof
WO1994028464A1
Polyvinyl alcohol film
WO2021132425A1